Bank Competition in the Middle East and Northern Africa Region - Anzoategui, Diego (2012)
This paper studies the extent of bank competition in the Middle East and Northern Africa (MENA) region during 1994-2008, using non-structural measures of competition such as the H-statistic and the Lerner index. Both these measures suggest that banking sector competition in MENA is lower relative to other regions and has not improved in recent years. An analysis of the determinants of competition across countries suggests that lower levels of competition in MENA are explained by a worse credit information environment and lower market contestability.